Germination and Seed Vigour of Indigenous Bean (Phaseolus Vulgaris) Genotype in Nepal - Uprety, Anupam; Dahal, Bhishma Raj; Shrestha, Bishal (SAARC Journal of Agriculture, 2021)
Bean is an important vegetable crop of Nepal but farmers of Jumla district of Nepal are experiencing low productivity, probably due to poor germination. Keeping these points in view, a study was conducted to determine the germination and seed vigour of various indigenous beans genotype of Jumla district during February to March, 2018. The promising lines of Jumli beans namely KBL-3, KBL-2, PB0002, PB0001, KBL-1 and farm saved KBL-3 were used under study. The experiment was laid in completely randomized design (CRD) with four replications and six treatments namely T1 = KBL-3, T2 = KBL-2, T3 = PB0002, T4 = PB0001, T5 = KBL-1 and T6 = Farm-saved KBL-3. Significant differences were observed in germination percentage, speed of germination, seed vigourindex and true leaf emergence among different lines of Jumli beans .The highest germination percentage (96%), seed vigour index (1367) and speed of germination (1.763) was found in the variety of KBL-3 whereas the lowest germination percentage (69%), seed vigour index (947) and speed of germination (0.968) were found in the variety of KBL-1. Days to true leaf emergence was found shortest in the KBL-3 (23.50) and longest in the farm saved KBL-3 (30.25). KBL-3 pureline of Jumli bean was found to be highly responsive to seed germination and vigour characteristics. Thus, it would be better to suggest the indigenous bean growing farmers of Jumla district to cultivate KBL-3 for better germination and seed vigour. SAARC J. Agri., 18(2): 67-75 (2020)